A Survey of Computational Approaches and Challenges in Multimodal Sentiment Analysis - Huddar, Mahesh G; Sannakki, Sanjeev S; Rajpurohit, Vijay S (International Journal of Computer Sciences and Engineering, 2019)
Most of the recent work in sentiment analysis is carried out on textual data. The text based sentiment analysis mainly relies on construction of word dictionaries, using machine learning techniques that learn and extract opinion from large text corpora. Text based sentiment analysis has numerous applications such as customer satisfaction analysis about a brand or product perception, to gauge voting intentions etc. With the rapid growth of social media, users post humongous volume of data in various modalities such as text, image, audio, and video. These multimodal data streams bring new opportunities for going beyond text based sentiment analysis and improving possible results. Since sentiment can be extracted from facial and vocal expressions, prosody and body posture, multimodal sentiment analysis offers new avenues in sentiment analysis. In multimodal sentiment analysis, sentiment is extracted from transcribed content, visual and vocal features. This survey defines sentiment, sentiment analysis, states problems and challenges in multimodal sentiment analysis and finally reviews some of the recent computational approaches used multimodal sentiment analysis.